Análise do ambiente de trabalho do enfermeiro de hospitais públicos - Oliveira, Priscila Braga de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The working environment is one of the influencing factors of service quality to the user. The hospital accreditation process evaluates the quality and contributes to the achievement of excellence. Correlating the working environment with quality certification can contribute to the knowledge in this subject. Among the possibilities of identifying the working environment of health organizations the source Nursing Work Index - Revised (NWI-R) has been used in different cultures and nursing practice environments. The NWI-R was translated, adapted and validated for the Brazilian culture and called Nursing Work Index - Revised - Brazilian version (B-NWI-R). This study aims to analyze the working environment of nurses from two public hospitals, compare their environment and understand the factors related to nurses' workplace that affect the work process. A study was conducted in quantitative and qualitative approach. The quantitative research covered two cross-sectional studies in parallel, with hospital nurses between January and September 2014. Hospital A was not accredited and Hospital B was accredited (level 1). Data collection was carried through a questionnaire with labor socio-demographic data and the B-NWI-R with 57 items and four areas: autonomy, control over the working environment, doctor and nurse relationship and organizational support. The reliability of such resource was measured by Cronbach's alpha. The test was answered by 106 nurses, 50 from Hospital A and 56 from Hospital B. The qualitative research adopted the content analysis, with eight nursing managers. Data collection used audio recorded and semi-structured interviews with the guiding question: According to your perspective, what are the factors related to the nursing working environment that interfere in the working process? The interviews lasted 30 minutes. The research was approved by the Research Ethics Committee, Platform Brazil No. 23304713.4.0000.5411. The ...

O ambiente de trabalho é um dos fatores intervenientes da qualidade assistencial ao usuário. Os processos de acreditação hospitalar avaliam a qualidade e contribuem para o alcance da excelência. Correlacionar o ambiente de trabalho com a certificação de qualidade pode contribuir com o conhecimento nessa temática. Dentre as possibilidades de identificar o ambiente de trabalho das organizações de saúde o instrumento Nursing Work Index - Revised (NWI-R) tem sido utilizado em diferentes culturas e ambientes da prática do enfermeiro. O NWI-R foi traduzido, adaptado e validado para a cultura brasileira e denominado Nursing Work Index - Revised - Versão Brasileira (B-NWI-R). Esse estudo tem como objetivo analisar o ambiente de trabalho do enfermeiro de dois hospitais públicos, comparar o ambiente de trabalho desses hospitais e compreender os fatores relacionados ao ambiente de trabalho do enfermeiro que mais interferem no processo de trabalho. Foi realizado estudo na abordagem quantitativa e qualitativa. Na quantitativa foram dois estudos transversais em paralelo, com enfermeiros assistenciais dos hospitais entre janeiro a setembro de 2014. O hospital A não era acreditado e o hospital B acreditado (nível 1). A coleta de dados foi por meio de um questionário com dados sóciodemográficos laborais e o B-NWI-R com 57 itens e quatro domínios: autonomia, controle sobre o ambiente, relacionamento médico e enfermeiro e suporte organizacional. A confiabilidade do instrumento foi medida pelo alpha de Cronbach. Responderam o instrumento 106 enfermeiros, 50 do hospital A e 56 do B. Na qualitativa adotou-se a análise de conteúdo, com oito gerentes de enfermagem. A coleta dos dados utilizou entrevistas audiogravadas e semiestruturadas com a questão norteadora: Segundo sua perspectiva, quais são os fatores relacionados ao ambiente de trabalho do enfermeiro que mais interferem no processo de trabalho deles? As entrevistas duraram...
Analysis of public hospital nurses' working environment
Keywords: Enfermagem; Enfermeiros - Satisfação no trabalho; Ambiente de trabalho; Humanização na saúde; Hospitais - Credenciamento; Nurses - Job satisfaction